Gut Microbiota and Atherosclerosis—Focusing on the Plaque Stability - Shen, Xinyi; Li, Lihua; Sun, Zhen; Zang, Guangyao; Zhang, Lili; Shao, Chen; Wang, Zhongqun (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVDs) are major causes of mortality and morbidity in the modern society. The rupture of atherosclerotic plaque can induce thrombus formation, which is the main cause of acute cardiovascular events. Recently, many studies have demonstrated that there are some relationships between microbiota and atherosclerosis. In this review, we will focus on the effect of the microbiota and the microbe-derived metabolites, including trimethylamine-N-oxide (TMAO), short-chain fatty acids (SCFAs), and lipopolysaccharide (LPS), on the stability of atherosclerotic plaque. Finally, we will conclude with some therapies based on the microbiota and its metabolites.